Bone Metastasis-Related MicroRNAs: New Targets for Treatment? - Zhao, Qian; Luo, Fengming; Ma, Junrong; Yu, Xijie (Current Cancer Drug Targets, 2015)
MicroRNAs (miRNAs) are a new class of small noncoding RNAs of 19–25 nucleotides that function as negative posttranscriptional gene regulators. MiRNAs hybridize to the 3’ untranslated region (UTR) of target mRNAs and repress translation or mediate mRNA cleavage. MiRNAs critically regulate tumorigenesis and progression by targeting oncogenes, tumor suppressor genes, or genes related to proliferation, angiogenesis, and apoptosis. Different tumor types and tumors at different stages exhibit unique miRNA profiles. MiRNAs show promise as potential biomarkers for cancer diagnostics, progression, and response to treatment. The role of miRNAs in promoting bone metastases is under investigated. We summarize recent findings on the mechanisms by which miRNAs may regulate bone metastatic spread of breast cancer, prostate cancer#140;lung cancer and multiple myeloma. We review similarities and differences in miRNA profiles that may explain the variety of molecular pathways underling metastatic spread to the skeleton in different cancers. Finally, we discuss the exciting potential of using miRNAs as diagnostics and therapeutic targets to reduce the risk of bone metastases in cancer, from the perspective of data provided by recent pre-clinical and clinical studies.
Keywords: multiple myeloma